Total carbon, total organic carbon, total inorganic carbon and total sulfur (solid-phase discrete samples) from IODP Hole 386-M0094A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Total carbon (TC), total organic carbon (TOC), total inorganic carbon (TIC) and total sulfur (TS) from solid-phase discrete samples of the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the onshore phase a set of solid-phase samples, with a volume of approx. 10 cubic centimeters each, were taken with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon and X-ray fluorescence. The bulk solid-phase samples were taken from the work halves of core sections at about one sample per meter on average. Unprocessed samples were then shipped to the MARUM - Center for Marine Environmental Sciences of the University of Bremen (Germany), where they were freeze-dried, ground and homogenized to a fine powder by ECORD Science Operator staff using a pestle and an agate mortar. For TC, TOC and TS an aliquot of approx. 100 mg from each sample was measured using a CS744 LECO carbon-sulphur analyzer. TIC was determined by subtracting TOC from TC. All data are reported in weight percentage per dry sample with an analytical precision. Total nitrogen (TN, aliquot of approx. 30 mg) was analyzed with a Vario EL3 CHNS analyzer by Elementar. Because of technical issues, TN was only measured on samples from Sites M0081 and M0082. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023